Comparative evaluation of traditional and improved farming practices in Tripura - YADAV, GULAB SINGH; DEBNATH, CHANDAN; DATTA, M; NGACHAN, S V; YADAV, J S; BABU, SUBHASH (The Indian Journal of Agricultural Sciences, 2013)
The improved farming with various animal and crop components can play a significant role in increasing manifoldproduction, income, and nutrition and employment opportunities of rural populations. The present survey work was carried out at sixty farmers’ plots covering a total area of 40.2 ha in Dhalai district of Tripura during the year 2012–13 to assess the production and income from traditional and improved methods of farming practised by the rural farm households. Production of seven different components like fish, paddy, piggery, dairy, poultry, vegetables and fruit crops production were employed in the investigation. The results revealed that the performance of all components is better in improved farming over traditional management. The average productivity of different components was significantly higher in improved farming as compared to the traditional farming. The improved farming system gave higher net return and benefit cost ratio to the farmers as compared to traditional farming. The overall result revealed that the improved practice with different crop and animal components is an excellent approach for sustainable production, income generation and employment opportunity of the resource poor rural households of Tripura.